In Vitro Study of Combined Application of Bevacizumab and 5-Fluorouracil or Bevacizumab and Mitomycin C to Inhibit Scar Formation in Glaucoma Filtration Surgery - Yuanyuan Zhang; Shaopin Zhu; Xun Xu; Lei Zuo (Journal of Ophthalmology)
This is an in vitro study conducted to observe the safety and antiscarring effects of combined application of bevacizumab (BVZ) and 5-fluorouracil (5-Fu) or BVZ and mitomycin C (MMC) during glaucoma filtration surgery (GFS). The cytotoxicity of drug combinations in human Tenon’s fibroblasts (HTFs) and human umbilical vein endothelial cells (HUVECs) was evaluated. Their effects on the levels of vascular endothelial growth factor (VEGF) in HUVECs, cell proliferation and migration in HTFs, and the expression of collagen type I alpha 1 (Col1A1) gene in HTFs were evaluated. In addition, the effects of combined drugs on VEGF(R) mRNA in HTFs were detected to explore the possible underlying drug mechanisms. The results showed that BVZ combined with 5-Fu demonstrated more significant antiscarring effects than BVZ or 5-Fu alone. However, the inhibitory effects of BVZ combined with MMC were similar to those of MMC alone. The cytotoxicity of the drug combinations was significantly greater than that of single drug, suggesting that combined application of BVZ and antimetabolites after GFS was safer when applied at different sites (such as subconjunctival injection at bilateral sides of the filtering bleb) or at varied time points.